Efficiency of Decentralized Road Investment and Pricing in a Multi-Jurisdictional City with Spillovers - Jan K. Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper shows that the inefficiency of fiscal decentralization in the presence of spillovers, a main tenet of the decentralization literature, is overturned in a particular transportation context. In a monocentric city where road (bridge) capacity is financed by budget-balancing user fees, decentralized capacity choices (made by individual zones within the city) generate the social optimum despite the presence of spillovers. This conclusion is closely tied to the famous self-financing theorem of transporation economics.
Keywords: H70; 330; decentralization; road pricing; congestion; spillovers